A PROPOSED FRAMEWORK FOR INVESTIGATING THE RELATIONSHIP BETWEEN UNIVERSITY COMMITMENT AND ETHICAL FINANCIAL BEHAVIOR AMONG MALAYSIAN UNDERGRADUATE STUDENTS - H, Saunders; K, Vehviläinen-Julkunen (Economics and Statistics Research Journal (ESRJ), 2022)
This paper examines the factors influencing ethical financial behavior among undergraduate students in Malaysia. The study focuses on the impact of financial knowledge, money attitude, financial self-efficacy, and locus of control on ethical financial behavior. The university years are a critical time for students to develop financial independence, and with limited financial constraints, students are more vulnerable to making unwise financial decisions leading to financial problems, stress, and bankruptcy. The paper proposes a framework that highlights the mediating role of university commitment in ethical financial behavior. The authors recommend that policymakers, authorities, and financial institutions play a vital role in producing a financially literate society and improving university commitment among students. Parents' participation is also crucial in nurturing children's financial knowledge and skills at a young age. The paper concludes that ethical financial behavior is significant in predicting student financial behavior, and a more diverse demographic must participate in surveys to accurately reflect Malaysian financial behavior and literacy